REHABILITATION OF GUILLAIN BARRE SYNDROME - Sibel Özbudak Demir,; Gülümser Aydın, (Archives of Rheumatology, 2001)
Guillain Barre Syndrome is an acute autoimmune disease of peripheral nervous system. The main feature is rapidly evolving motor weakness combined in many patients with sensory loss. After a plateau phase, spontaneus recovery starts, but it is not always complete. Approximately %40 of patients who are hospitalized with GBS will require admission to inpatient rehabilitation. Ventilatory support has been correlated with longer length of stay and increased cost for inpatient rehabilitation. Other factors that affect rehabilitation are dysautonomia, cranial nerve involvement and various medical complications. Deafferent pain syndrome is common in early stage of recovery. Multipl medical complications, including deep venous trombosis, joint contractures, hypercalcemia due to immobilization and pressure sores may develop. Overfatiguing the affected motor unit has been clinically associated with paradoxical weakness and may impede recovery. Little is known known about the long term outcomes of disability caused by GBS. Rehabilitation programme is similar to that performed in postpolio syndrome and spinal cord injury.